2006
DOI: 10.1097/01.mat.0000225894.61493.2f
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytes-Depleting Filters Preferentially Remove Activated Leukocytes and Reduce the Expression of Surface Adhesion Molecules during the Simulated Extracorporeal Circulation of Human Blood

Abstract: The effect of leukocyte-depleting filters on the total and activated leukocyte counts and the expression of surface adhesion molecules CD11b, CD18, and CD62L during the in vitro extracorporeal circulation of human blood was studied. A 200 ml blood sample was taken from 10 patients undergoing CABG surgery. The blood was circulated for 60 minutes within an experimental extracorporeal circuit. A leukocyte-depleting filter was attached in five circuits (filtered group). In five other circuits, no filter was used (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…TNF-α was measured because this cytokine has been implicated as a mediator of RI and has extremely widespread effects on inflammation, cellular proliferation, and differentiation (13). In the heart, reactive oxygen species are produced under ischemic conditions which subsequently increase TNF-α production, leading to contractile dysfunction, hypertrophy, fibrosis, and cell death (14). In the liver, RI seems to be similarly mediated, and both neutrophils and inflammatory mediators, including TNF-α, are known to play important roles (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α was measured because this cytokine has been implicated as a mediator of RI and has extremely widespread effects on inflammation, cellular proliferation, and differentiation (13). In the heart, reactive oxygen species are produced under ischemic conditions which subsequently increase TNF-α production, leading to contractile dysfunction, hypertrophy, fibrosis, and cell death (14). In the liver, RI seems to be similarly mediated, and both neutrophils and inflammatory mediators, including TNF-α, are known to play important roles (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…They also found that serum components that bind adhesion receptors, including fibronectin (VLA-4 integrin ligand) and hyaluronic acid (CD44 ligand), are also critical for lymphocyte adhesion [32]. Alexiou and coworkers observed that LRS filters selectively bound to white blood cells that expressed the CD11b integrin and CD62L, which are found on a subset of activated lymphocytes and naïve/central memory T cells, respectively [33]. In addition to interactions between the LRS cone matrix and adhesion receptors on the T cells, the LRS cones also concentrate T cells in specific regions of the filter.…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested that leukocyte depletion filters preferentially remove activated leukocytes. Improvement in lung function was evident only in the early postoperative phase, but this did not lead to decreasing mortality or better clinical outcomes [ 72 ]. The use of ultrafiltration or modified ultrafiltration techniques at the end of surgery may reduce postoperative oedema specifically that of lungs resulting in better oxygenation and improved lung compliance postoperatively.…”
Section: Pulmonary Protection Strategiesmentioning
confidence: 99%